Pengembangan Prototipe Kamus CCU (Cross Cultural Understanding) bagi Pemelajar BIPA (Bahasa Indonesia bagi Penutur Asing) dari China - Amalia, Rina; Indarti, Titik; Raharjo, Resdianto Permata (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This study aims to develop a prototype CCU dictionary for BIPA students from China. In addition to language, BIPA students need to understand Indonesian culture because language and culture are related. Language can be mastered well if the culture that accompanies it is also well understood. This research is a mixed study with the ADDIE model development method (Analysis, Design, Development, Implementation, and Evaluation) to the development stage due to the limited time in this study. Needs analysis is done by using questionnaires and literature study. Then, the design and development of this prototype is carried out by taking into account the aspects of the material, presentation, as well as language and readability. The results of this study revealed that most BIPA students experienced culture shock because of the differences in Indonesian culture and the culture of the student country. There are 45 cross cultural understandings that BIPA students from China need to understand. The cross cultural understanding consists of 16 cultural similarities and 29 cultural differences. These cultural comparisons are presented in this developed CCU dictionary prototype. This CCU dictionary prototype is designed to be a material for creating applications as electronic learning media that can be accessed offline and contain images, audio, audio visuals, and text in it. This CCU dictionary prototype contributes to the BIPA teaching and learning process and it is beneficial for students, teachers, and institutions.